A PEARL Study Analysis of National Neonatal, Early Neonatal, Late Neonatal, and Corrected Neonatal Mortality Rates in the State of Qatar during 2011: A Comparison with World Health Statistics 2011 and Qatar's Historic Data over a Period of 36 Years (1975-2011) - Rahman, Sajjad (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: To prospectively ascertain Qatar's national Neonatal Mortality Rate (NMR), Early Neonatal Mortality Rate (ENMR), and Late Neonatal Mortality Rate (LNMR) during 2011, compare it with recent data from high-income countries, and analyze trends in Qatar's NMR's between 1975 and 2011 using historic data. STUDY DESIGN: A National prospective cohort-study. MATERIALS AND METHODS: National data on live births and neonatal mortality was collected from all public and private maternity facilities in Qatar (1(st) January-December 31(st) 2011) and compared with historical neonatal mortality data (1975-2010) ascertained from the database of maternity and neonatal units of Women's Hospital and annual reports of Hamad Medical Corporation. For inter country comparison, country data of 2009 was extracted from World Health Statistics 2011 (WHO) and the European Perinatal Health report (2008). RESULTS: A total of 20583 live births were recorded during the study period. Qatar's national NMR during 2011 was 4.95, ENMR 2.7, LNMR 2.2, and cNMR 3.33. Between 1975 and 2011, Qatar's population increased by 10-fold, number of deliveries by 7.2 folds while relative risk of NMR decreased by 87% (RR 0.13, 95% CI 0.10-0.18, P<0.001), ENMR by 91% (RR 0.09, 95% CI 0.06-0.12, P<0.001) and LNMR by 58% (RR 0.42, 95% CI 0.23-0.74, P=0.002). The comparable ranges of neonatal mortality rates from selected high-income West European countries are: NMR: 2-5.7, ENMR 1.5-3.8, and LNMR 0.5-1.9. CONCLUSIONS: The neonatal survival in the State of Qatar has significantly improved between 1975 and 2011. The improvement has been more marked in ENMR than LNMR. Qatar's current neonatal mortality rates are comparable to most high-income West European countries. An in-depth research to assess the correlates and determinants of neonatal mortality in Qatar is indicated.